Study of Ionic Liquids (AIL and PIL) Viscosity and its Functional Groups under Heat Treatment on Cutting Tool Surface Using Fourier- Transform Infrared Spectroscopy (FTIR) - Mona Alis, Md Yasser; Zaidi, Embong; Erween, Abd Rahim; Amiril Sahab, Abdul Sani; Kamaruddin, Kamdani (Trans Tech Publications, Switzerland, 2019)
This study was conducted to investigate the efficiency of Minimum Quantity Lubrication (MQL) technique by using Modified Jatropha Oil (MJO) bio-based lubricant with the presence of 10% Ammonium Ionic Liquid (MJO+AIL10%) and 1% Phosphonium Ionic Liquid (MJO+PIL1%) additives respectively at various temperature of 200 C, 300 C and 400 C heat treatment to determine the ability to exhibit corrosion and wear throughout the process. Fourier-Transform Infrared Spectroscopy (FTIR) analysis revealed prominent peaks of functional groups in these bio-lubricants; esters (C-O) and (C=O), alkanes (C-H), hydroxide (O-H), and nitrile groups deposited on the cutting tool surface. Initially, nitrile group is detected on cutting tool surface without lubricants at 2200 cm−1 to 2300 cm−1 absorption band reduced to lower intensity and most likely concealed by MJO+AIL10% compared to MJO+PIL1% where the nitrile group remains reflected in FTIR spectrum. In this work, it is proved that MJO+AIL10% has higher viscosity as compared to MJO+PIL1%. in the context of functional groups and supported the previous study on MJO+AIL10% as corrosion inhibitor.